1991
DOI: 10.1017/s0714980800007248
|View full text |Cite
|
Sign up to set email alerts
|

Informal Caregiving: Correlates of Perceived Burden

Abstract: RÉSUMÉDe nombreuses recherches concluent que les aidants naturels de personnes âgées en perte d'autonomie éprouvent un fardeau associé à leur situation. Les principaux facteurs influençant ce fardeau sont ici passés en revue et regroupés en quatre catégories: variables liées aux tâches effectuées par l'aidant, caractéristiques de la personne âgée, caractéristiques de l'aidant et variables interactionnelles caractérisant la relation entre l'aidant et l'aidé. L'article présente les résultats d'une recherche cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 17 publications
0
23
1
4
Order By: Relevance
“…Both objective and subjective burdens are higher for female than for male caregivers (Chang & White-Means, 1991;Miller & Montgomery, 1990;Morris, Woods, Davies, & Morris, 1991;Mui, 1995a). As one might expect, degree of burden can be predicted by the level of assistance required, the amount of dependency, the extent of individual responsibility for the dependent, and the availability of help from others (Jutras & Veilleux, 1991). McKinlay, Crawford, & Tennstedt (1995), using data from the 7-year longitudinal Massachusetts Elder Health Program, showed that 61 percent of carers rated their caregiving responsibilities to be the most disruptive aspect of their lives, and this was particularly likely if they lived with the person cared for.…”
Section: Impact Of Care: Physical and Emotional Burdenmentioning
confidence: 93%
“…Both objective and subjective burdens are higher for female than for male caregivers (Chang & White-Means, 1991;Miller & Montgomery, 1990;Morris, Woods, Davies, & Morris, 1991;Mui, 1995a). As one might expect, degree of burden can be predicted by the level of assistance required, the amount of dependency, the extent of individual responsibility for the dependent, and the availability of help from others (Jutras & Veilleux, 1991). McKinlay, Crawford, & Tennstedt (1995), using data from the 7-year longitudinal Massachusetts Elder Health Program, showed that 61 percent of carers rated their caregiving responsibilities to be the most disruptive aspect of their lives, and this was particularly likely if they lived with the person cared for.…”
Section: Impact Of Care: Physical and Emotional Burdenmentioning
confidence: 93%
“…Interestingly, Jutras & Veilleux (64) reported that husband caregivers experience more burden then wife caregivers, even though wives were providing more assistance. Kane et al (22) also reported that men struggle in the caregiving role.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that adult children, especially daughters and daughters-in-law, are often involved in caring for and tending to the needs of their elderly or infirm parent(s) (Allan, 1988;Brody, 1990;Jutras & Veilleux, 1991;Pohl et al, 1995;Raveis & Pretter, 2005). Society, culture, and religious traditions enforce the predominance of adult daughters and daughters-in-law as caregivers (Brakman, 1994;WardGriffin, 2004).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Attention to family caregiving has increased with the escalation of situations in which the impaired or chronically ill elderly are taken care of by family members in the community (Brody, 1990;Pepin, 1992). With shorter hospital admissions and the resultant pressure on community-based care, families are expected to assume major responsibility of care of its members at home (Boland & Sims, 1996;Faison, Faria, & Frank, 1999;Jutras & Veilleux, 1991;Pepin, 1992;Rutman, 1996). Although care has moved from institutions to communities, the rather slippery notion of community care tends to mean unpaid care sustained by families (Aronson, 1991;Jaffe & Blakley, 2000).…”
mentioning
confidence: 99%